2015
DOI: 10.5539/ijef.v7n5p109
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cash Flow on Share Price of the Jordanian Commercial Banks Listed in Amman Stock Exchange

Abstract: This study aims at examining the effect of cash flow on share price of the Jordanian commercial banks listed in Amman stock exchange, through measuring the effect of operational, investing and financing cash flow, as individual or jointly on the share price of the Jordanian commercial banks.In order to achieve the objectives of the study a sample of twelve Jordanian commercial banks were chosen through intentional sampling approach, out of fifteen banks which constitutes the total number of the Jordanian comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
9
2
Order By: Relevance
“…The finding of this study revealed that positive but insignificant relationship between operating cash flow and value of listed manufacturing firms in Nigeria. This is also the position of Khanji and Siam (2015) in the context of Jordan, while Al-Zararee and Al-Azzawi (2014), Girish and Desai (2017); Lyndon and Paymaster (2016), as well as Wanjiru and Oluoch (2016) reported significant positive impact. On the other hand, the studies of Kadioglu et al (2017); Brush et al (2000); Park and Jang (2013); Heydari et al (2014); and Wang (2010) reported significant negative effect of free cash flow on firm value (Tobin's Q) but Khraywesh, (2001) concluded that no significant relationship exist between the net cash flows and stock's market value.…”
Section: Discussionmentioning
confidence: 71%
“…The finding of this study revealed that positive but insignificant relationship between operating cash flow and value of listed manufacturing firms in Nigeria. This is also the position of Khanji and Siam (2015) in the context of Jordan, while Al-Zararee and Al-Azzawi (2014), Girish and Desai (2017); Lyndon and Paymaster (2016), as well as Wanjiru and Oluoch (2016) reported significant positive impact. On the other hand, the studies of Kadioglu et al (2017); Brush et al (2000); Park and Jang (2013); Heydari et al (2014); and Wang (2010) reported significant negative effect of free cash flow on firm value (Tobin's Q) but Khraywesh, (2001) concluded that no significant relationship exist between the net cash flows and stock's market value.…”
Section: Discussionmentioning
confidence: 71%
“…It is highly possible that there would be no match between net income in income statements and operating cash flows in cash flow statements due to non-cash expenses such as depreciation (Khanji and Siam, 2015). Operating cash flows could be greater or less than net income.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…This implies that accounting information serves as a guide to investors' investment decisions. Khanji and Siam (2015) indicated a limited effect of operating, investing, and financing cash flows on Jordanian commercial banks' share market values. Consequently, more concern is needed regarding cash flow behavior when assessing share prices.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…The results of the study showed that there is a significant effect of both operating cash flows attributable to total assets and operating cash flows attributable to total liabilities on the financial performance measured by earnings per share. The study of (Khanji& Siam, 2015) examined the effect of operating, investment and financing cash flow on the shares market value of (13) commercial banks listed on the Amman Stock Exchange during the period 2010-2013. The results of the study showed a significant positive effect of all operating, financing and investment cash flows on the shares market value.…”
Section: Literature Reviewmentioning
confidence: 99%